ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI KABUPATEN PATI TAHUN 1990-2019 - Tarisa Tarisa; Hutajulu Dinar Melani (JURNAL LITBANG KOTA PEKALONGAN, 2022)
The purpose of this study is to analyze the long-term and short-term effects of paddy field area, rice prices and rainfall on rice production in Pati Regency. This study uses the ARDL analysis method. Secondary data obtained from the Central Statistics Agency 1990-2019. From the calculation using ARDL, it was found that the rice price and rainfall variables had a positive and significant effect on rice production, both in the long term and in the short term. Meanwhile, the variable area of ??land does not significantly affect the yield of rice production, both in the long and short term.  Keywords: Production, land area, price, rainfall